2016
DOI: 10.1002/2016jc012166
|View full text |Cite
|
Sign up to set email alerts
|

Upwelling intensity modulates N2O concentrations over the western Indian shelf

Abstract: Repeat measurements of dissolved nitrous oxide (N2O) along two transects of the western continental shelf of India in 2012 revealed high concentrations of 45 ± 32 nM (off Kochi) and 73 ± 63 nM (off Mangalore) during the summer monsoon (SM). N2O concentrations increased nonlinearly during the peak of the SM upwelling, when low O2 (<25 µM) conditions prevailed in the water column. Off Kochi, N2O levels fell gradually from the fall intermonsoon (20 ± 8 nM) to the winter monsoon (8.8 ± 2 nM) and remained low (9.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Low P * at NF-a could also be either due to the consumption of phosphate by diazotrophy or due to the upwelling, which starts during May as evidenced in the temperature profile at NF-a (Figure 2). Upwelling would create low oxygen just below MLD Sudheesh et al, 2016), as observed at NF-a (Figure 2). However, high P * -values would have been expected in low oxygen water but deeper water, as evidenced from the P * profiles (Table 1), has low P * -possibly because of the remineralization of diazotrophy dominated organic matter (high N:P ratio) in the deeper depths.…”
Section: Nutrientsmentioning
confidence: 97%
“…Low P * at NF-a could also be either due to the consumption of phosphate by diazotrophy or due to the upwelling, which starts during May as evidenced in the temperature profile at NF-a (Figure 2). Upwelling would create low oxygen just below MLD Sudheesh et al, 2016), as observed at NF-a (Figure 2). However, high P * -values would have been expected in low oxygen water but deeper water, as evidenced from the P * profiles (Table 1), has low P * -possibly because of the remineralization of diazotrophy dominated organic matter (high N:P ratio) in the deeper depths.…”
Section: Nutrientsmentioning
confidence: 97%
“…However, this was so far the only report on the occurrence of hydrogen sulfide in Arabian Sea (Naqvi et al, 2000;Swallow, 1984) until Naqvi et al (2000) discovered an anoxic event that developed along the western Indian coast off Mumbay during the late summer and autumn in 1999. Such strong events seem to emerge not every year (Gupta et al, 2016;Sudheesh et al, 2016) but mass mortalities occur, in between, also along the eastern Indian coast in the Bay of Bengal (Altieri et al, 2017). The spreading of 'dead zones' in coastal regions is apparently a global phenomenon that does not spare the Indian coast in the Arabian Sea and the Bay of Bengal (Altieri et al, 2017;Diaz & Rosenberg, 2008).…”
Section: Recent Trends In the Bay Of Bengal And The Arabian Seamentioning
confidence: 99%
“…The width of Cochin inlet is about 450 m, and Azhikode has a narrow width of 250 m respectively. Due to anthropogenic activity, Cochin estuary receives 1.04 × 10 5 m 3 of untreated industrial effluents and 260 m 3 of domestic or sewage wastes, which alters the bio-geochemical properties of coastal water off Cochin (Gupta et al, 2016;Sudheesh et al, 2016). The coastal waters off Cochin in SEAS is typical optically complex Case 2 water (Minu et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…Table 1 presents the variability in water quality and optical properties during SIM, SWM, FIM and WM along the coastal waters off Cochin. The Barmouth region (B1 station) was influenced by freshwater discharge from Cochin estuary during SWM (Gupta et al, 2016;Sudheesh et al, 2016) and accordingly in our study, salinity showed a lower value at B1 station ranged between 13.43-31.62 (psu) with an average value of 22.53 ± 12.87 (psu) during SWM and similarly salinity showed a higher value at B3 station ranged between 33.62-34.53 (psu) with an average value of 33.93 ± 0.52 (psu) during WM. The value of pH was higher at B4 station varied from 8.2 to 8.3 with an average value of 8.25 ± 0.07 during FIM and showed a lower value at B1 station varied from 7.5 to 7.7 with an average value of 7.57 ± 0.12 during SIM.…”
Section: Total Suspended Matter Concentrationmentioning
confidence: 99%
See 1 more Smart Citation